Diagnóstico de comunicación externa de la Red de Comercio Justo “Allí Tarpuk Kuna”, para la promoción de los productos agropecuarios en la parroquia de Cangahua, cantón Cayambe, provincia de Pichincha, año 2023. - Silva Lombeida, Anderson Xavier (2024)
The present research work examines the communication factors of the Fair Trade Network “Allí Tarpuk Kuna” in the Cangahua parish, Cayambe canton, province of Pichincha regarding its external communication and the use of its corporate identity in positioning towards the public; For this reason, the diagnosis of external communication to this trade network was carried out. These activities allow us to optimize the identity of the brand and promote the promotion of agricultural products offered by this organization, in the year 2023. This work demonstrates the theoretical support of the communication field and includes a theoretical framework that refers to: identity, image, strategies, communication, brand, among other concepts that allow us to more thoroughly understand communication from the corporate field. The types of research applied in this project are qualitative and quantitative methods, which helped us analyze and collect information from the interviews, survey and observation sheet